CREATING AN ELECTRONIC MANUAL FOR THE USE OF NATIONAL FOLK GAMES IN THE PHYSICAL EDUCATION OF STUDENTS: https://doi.org/10.5281/zenodo.14033358 - Abdualiyev , Ibrohim (Journal of Contemporary World Studies, 2024)
This article explores the possibilities of increasing physical activity of students and contributing to the understanding of cultural values ​​through the use of national folk games in the process of physical education. National folk games serve not only to develop students’ physical skills, but also to make them understand and appreciate national values. The research examines the effect of including national folk games in physical education lessons, the effect on students’ physical fitness and motivation level. Also, the process of creating an electronic manual on the successful use of national folk games in the physical education of students and its advantages will be covered. The results of the research are presented in the form of tables, and scientifically based conclusions are drawn on the physical and cultural importance of folk games for students. This article is of practical importance for physical education teachers and pedagogical specialists.